Metodelatihan meningkatkan kekuatan dan tenaga atlet profesional wanita - Putri, Vivi Novia Eka; Yudiana, Yunyun; Sidik, Dikdik Zafar; Nugraha, Eka; Jatmiko, Tutur (Universitas Nusantara PGRI Kediri, 2024)
Well-planned and structured physical training is essential for enhancing athletic performance, particularly in sports like beach volleyball that demand strength and power. This research aims to assess the effects of practice methods on the strength and power of female athletes in the Indonesian National Beach Volleyball Team. This research employs an experimental method with a pre-test and post-test design. This study used a total sampling technique to obtain 6 female athletes from the Indonesian National Beach Volleyball Team with an age range of 19-27 years. The practice method is the OPT (Optimum Performance Training) method. This research was carried out for 12 weeks with a training frequency of 3 times a week. Strength was evaluated using the 1 RM test, and power was measured with the RAST test. Analysis of this research data using SPSS 22 includes the normality test and the independent ttest. The independent T-test results indicated that the Sig value for strenght 0.01 and power 0.00 was less than 0.05, demonstrating a significant difference between the pre-test and post-test. The research concludes that a 12-week OPT training program significantly enhances the strength and power of female athletes on the Indonesian National Beach Volleyball Team. Based on the results of this study, the contribution that can be given to coaches is that they can apply OPT to increase the strength and power of athletes in beach volleyball and other sports.